Methodological Design and Validation of Instruments for Integrated Measurement of Cognitive and Affective Variables in Initial Mathematics Teacher Education - Aguerrea, Maitere (2025)
[Objective] This study is intended to design and validate instruments for assessing mathematical errors, math anxiety, and visuospatial abilities in prospective mathematics teachers, to generate information that relates these variables to learning quality, from a gender perspective. [Methodology] This is a quantitative, non-experimental study with a descriptive, correlational scope and a cross-sectional design. The process included three stages: first, the design of two preliminary instruments—one with 32 items to measure math anxiety and another with 52 items to assess mathematical difficulties, errors, and spatial abilities. In the second stage the instruments were validated by experts, and finally, a pilot test was conducted, after which the items were revised and improved. [Results] The process resulted in three instruments: one to measure math anxiety (20 items, reliability = 0.825), one to assess mathematical errors and difficulties (41 items, reliability = 0.973), and another to measure visuospatial ability (9 items, reliability = 0.982). [Conclusions] The instruments developed allow for valid and reliable diagnosis of mathematical errors, math anxiety, and visuospatial abilities in initial teacher education. This information supports the development of equitable pedagogical strategies by addressing variables that affect performance and gender gaps, and opens new lines of research on their impact on teacher training trajectories.